Answer:
[tex]x_{1} =[/tex] [tex]\frac{5 + \sqrt{10} }{3}[/tex] and [tex]x_{2} =[/tex] [tex]\frac{5 - \sqrt{10} }{3}[/tex]
Step-by-step explanation:
3x^2-10x+5=0
[tex]x_{1}[/tex] = [tex]\frac{10 + \sqrt{10^{2}-4*3*5 } }{2*3}[/tex] [tex]x_{2} =[/tex] [tex]\frac{10 - \sqrt{10^{2}-4*3*5 } }{2*3}[/tex]
[tex]x_{1} =[/tex] [tex]\frac{10 + \sqrt{100-60} }{6}[/tex] [tex]x_{2} =[/tex] [tex]\frac{10 - \sqrt{100-60} }{6}[/tex]
[tex]x_{1} =[/tex] [tex]\frac{10 + \sqrt{40} }{6}[/tex] [tex]x_{2} =[/tex] [tex]\frac{10 - \sqrt{40} }{6}[/tex]
[tex]x_{1} =[/tex] [tex]\frac{10 + 2\sqrt{10} }{6}[/tex] / 2 [tex]x_{2} =[/tex] [tex]\frac{10 - 2\sqrt{10} }{6}[/tex] / 2
[tex]x_{1} =[/tex] [tex]\frac{5 + \sqrt{10} }{3}[/tex] [tex]x_{2} =[/tex] [tex]\frac{5 - \sqrt{10} }{3}[/tex]